FORMULATION AND CHARECTERISATION OF COLON TARGETED TIME DEPENDENT MICROSPHERES OF CAPECITABINE FOR COLORECTAL CANCER - Agrawal, Dilip; Ranawat, M. S. (Asian Journal of Pharmaceutical Research and Development, 2013)
The aim of the present work was to prepare the colon-targeting microspheres of Capecitabine (CPB) for the treatment of colorectal cancer to reduce dosing frequency and improve patient compliance. Time-dependent polymer Eudragit RL100, RS100 separately and in combination (1:1) was used to formulate the microspheres by emulsion solvent diffusion technique using varying drug – polymer ratios (1:1 to 1:5). Microspheres were evaluated for particle size, shape, flow properties, surface morphology by scanning electron microscopy, yield, drug content, and in vitro drug release behavior and found to be significantly affected by polymer concentration. The formulated microspheres were discrete, almost spherical with somewhat folded and invaginated surface, and with good flow properties. CPB-loaded microspheres demonstrated good entrapment efficiency (of 55.43±1.54% to 84.08±1.62). The release study was done in simulated gastrointestinal fluids for 2 hrs in SGF (pH 1.2), for 3 hrs in SIF (pH 6.8) and up to 24 hrs in SCF (pH 7.4) and time based formulations showed lag time of 4hrs protect the drug from being released 4 hrs and efficiently released in colon (97.92%). Formulation RLRS4 gave most promising result among all formulations (3.62% release at end of 4 hrs and 94.10% at the end of the study). It is concluded from the present study that time dependent Eudragit microspheres are promising carriers for oral colon-targeted delivery of CPB for colorectal cancer.